Preterism, futurism or historicism? : a theological evaluation of three interpretive schools of Apocalyptic Prophecy within the doctrine of the last things - Stander, Reinhardt (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.